2013
DOI: 10.2478/s11535-013-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive phenotypic plasticity of gypsy moth digestive enzymes

Abstract: The adaptiveness of plasticity of digestive enzyme responses to allelochemical stress was tested on 32 full-sib families of gypsy moth larvae from an oak forest population (the Quercus population) and 26 families from a locust-tree forest (the Robinia population), reared either on control diet, or on tannin-supplemented diet. Using the duration of larval development as an indirect measure of fitness, phenotypic selection analyses revealed that lower specific activities of total proteases and trypsin, and highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Conversely, we found no consistent pattern of selection on phenotypic plasticity between female and male fitness components. Although adaptive plasticity has become widely recognized as an important component of phenotypic response to variations in environmental factors (e.g., Baythavong and Stanton, 2010;Mrdaković et al, 2014;Via et al, 1995), this appears to be the first study that may demonstrate possible selection on phenotypic plasticity and costs of plasticity in an insect species in response to variations in host-feeding sources.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Conversely, we found no consistent pattern of selection on phenotypic plasticity between female and male fitness components. Although adaptive plasticity has become widely recognized as an important component of phenotypic response to variations in environmental factors (e.g., Baythavong and Stanton, 2010;Mrdaković et al, 2014;Via et al, 1995), this appears to be the first study that may demonstrate possible selection on phenotypic plasticity and costs of plasticity in an insect species in response to variations in host-feeding sources.…”
Section: Discussionmentioning
confidence: 94%
“…In the aphid Myzus persicae, strong selection for larger body size occurred among individuals reared on an unfavorable host plant (Peppe and Lomônaco, 2003), whereas in the gypsy moth Lymantria dispar phenotypic selection analyses revealed that specific activities of digestive enzymes were adaptive (Mrdaković et al, 2014).…”
Section: Selection On Phenotypic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal effects are in turn a special form of phenotypic plasticity where the transmission of maternal factors may affect the phenotype of the offspring (Mousseau & Dingle, ). For example, it has been reported that Lymantria disspar L. (Lepidoptera: Erebidae) expresses plasticity in digestive enzyme activity, which allow the insect to feed on different hosts’ foliage that contains different allelochemicals (Lazarevic et al ., ; Mrdakovic et al ., ). Furthermore, this kind of adaptation may be reversed if the conditions return to their original state (Thompson, ).…”
Section: Introductionmentioning
confidence: 97%
“…Because hsp70 is a plasticity gene, understanding the function of hsp70s could supply a good theoretical foundation for understanding insect adaptability to the environment [28] , [29] , [30] . To date, the homologous genes of hsp70s in relation to phenotypic plasticity have been studied in Rhagoletis cerasi , Calliphora vicina , Lymantria dispar and Melitaea cinxia [19] , [31] , [32] , [33] . However, the variation between conspecifics of different geographical populations has not been widely assessed [34] .…”
Section: Introductionmentioning
confidence: 99%